Wire and arc additive manufacturing of aluminum alloy lattice structure. (February 2020) - Li, Yongjie; Yu, Shengfu; Chen, Ying; Yu, Runzhen; Shi, Yusheng
Highlights: Wire and arc additive manufacturing (WAAM) has been used to manufacture lattice structures. The struts diameter of lattice structure was controlled by the size and number of droplets. The droplet size was controlled by the current, voltage, and period within a pulse period. The struts angle of lattice structure was controlled by the inter-layer lift and offset of the arc torch. Demonstration of aluminium alloy lattice structure was fabricated using WAAM technology via the manufacturing strategy. Abstract: Wire and arc additive manufacturing (WAAM) has been used to manufacture ER2319 aluminum alloy lattice structure, whereas a relationship of the struts diameter of lattice structure with the size and number of droplets, struts angle with the inter-layer lift and offset of the arc torch was developed. The manufacturing strategy of lattice structure by WAAM was formulated, and the aluminum alloy lattice structure demonstration was prepared where compressive properties were measured. The results show that the size of the droplet can be controlled by adjusting the current, voltage, and period within a pulse period; and then the struts diameter can be controlled by adjusting the size and number of droplets. The struts with a diameter of no less than 2.50mm were manufactured by WAAM, and its relative error was less than 2.0%. The struts angle can be controlled by adjusting the inter-layer lift and offset of the arc torch. The angle of the strut was from 15° to 90°, and its relative error was below 4.0%. A 3-layer pyramid lattice structure demonstration of the aluminum alloy composed of struts with a diameter of 3 mm and an angle of 45° was fabricated by WAAM. The average compressive strength of ER2319 aluminum Alloy lattice structure was 58.53 MPa.